Genetic Determinants of Serum Calcification Propensity and Cardiovascular Outcomes in the General Population - de Haan, Amber; Ahmadizar, Fariba; van der Most, Peter J.; Thio, Chris H. L.; Kamali, Zoha; Ani, Alireza; Ghanbari, Mohsen; Chaker, Layal; van Meurs, Joyce; Ikram, M. Kamran; van Goor, Harry; Bakker, Stephan J. L.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Serum calciprotein particle maturation time (T50), a measure of vascular calcification propensity, is associated with cardiovascular morbidity and mortality. We aimed to identify genetic loci associated with serum T50 and study their association with cardiovascular disease and mortality. Methods: We performed a genome-wide association study of serum T50 in 2,739 individuals of European descent participating in the Prevention of REnal and Vascular ENd-stage Disease (PREVEND) study, followed by a two-sample Mendelian randomization (MR) study to examine causal effects of T50 on cardiovascular outcomes. Finally, we examined associations between T50 loci and cardiovascular outcomes in 8,566 community-dwelling participants in the Rotterdam study. Results: We identified three independent genome-wide significant single nucleotide polymorphism (SNPs) in the AHSG gene encoding fetuin-A: rs4917 (p = 1.72 × 10−101), rs2077119 (p = 3.34 × 10−18), and rs9870756 (p = 3.10 × 10−8), together explaining 18.3% of variation in serum T50. MR did not demonstrate a causal effect of T50 on cardiovascular outcomes in the general population. Patient-level analyses revealed that the minor allele of rs9870756, which explained 9.1% of variation in T50, was associated with a primary composite endpoint of all-cause mortality or cardiovascular disease [odds ratio (95% CI) 1.14 (1.01–1.28)] and all-cause mortality alone [1.14 (1.00–1.31)]. The other variants were not associated with clinical outcomes. In patients with type 2 diabetes or chronic kidney disease, the association between rs9870756 and the primary composite endpoint was stronger [OR 1.40 (1.06–1.84), relative excess risk due to interaction 0.54 (0.01–1.08)]. Conclusions: We identified three SNPs in the AHSG gene that explained 18.3% of variability in serum T50 levels. Only one SNP was associated with cardiovascular outcomes, particularly in individuals with type 2 diabetes or chronic kidney disease.